1990
DOI: 10.1002/bem.2250110206
|View full text |Cite
|
Sign up to set email alerts
|

Proflavin and microwave radiation: Absence of a mutagenic interaction

Abstract: The potential ability of radiofrequency electromagnetic radiation (RFR) in the microwave range to induce mutagenesis, chromosomal aberrations, and sister chromatid exchanges in mammalian cells is being explored in our laboratories. In addition, we have also been examining the ability of simultaneous exposure to RFR and chemical mutagens to alter the genotoxic damage induced by chemical mutagens acting alone. We have performed experiments to determine whether there is an interaction between 2.45-GHz, pulsed-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…Several studies (Szmigielski et al, 1982;Scarfi et al, 1996;Maes et al, 1997;Pakhomova et al, 1997) have suggested that microwaves can have an epigenetic effect in vivo, and that they can exacerbate the genotoxicity of ionizing radiation or cancer-inducing substances, or potentiate other epigenetic factors (IEGMP, 2000). However, the evidence for an epigenetic effect of microwaves is equivocal since some studies have failed to reproduce the positive results reported by others (Ciaravino et al, 1987(Ciaravino et al, , 1991Meltz et al, 1989Meltz et al, , 1990Cain et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies (Szmigielski et al, 1982;Scarfi et al, 1996;Maes et al, 1997;Pakhomova et al, 1997) have suggested that microwaves can have an epigenetic effect in vivo, and that they can exacerbate the genotoxicity of ionizing radiation or cancer-inducing substances, or potentiate other epigenetic factors (IEGMP, 2000). However, the evidence for an epigenetic effect of microwaves is equivocal since some studies have failed to reproduce the positive results reported by others (Ciaravino et al, 1987(Ciaravino et al, , 1991Meltz et al, 1989Meltz et al, , 1990Cain et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001. Thus, there is still no conclusive answer as to whether exposure to microwaves is clastogenic, i.e., whether they can direct or indirectly increase the frequency of chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Very detailed work in this area has been reported by Meltz et al [1989Meltz et al [ , 1990. In both independently performed series of investigations, L5178Y mouse leukemic cells were exposed to a 2450 MHz pulsed wave signal for 4 h. The mean SARs [30 W/kg in Meltz et al, 1989;40 W/kg in Meltz et al, 1990] were such that the temperature in the medium increased above the initial temperature of 37 8C during the 4 h exposure period.…”
Section: Induction Of Micronucleimentioning
confidence: 99%
“…A lack of effects of RF exposure on mutation frequency has dent increase in the progression or development of spontaneous mammary or chemically induced skin tualso been reported in a number of test samples including yeast [Dardalhon et al, 1981[Dardalhon et al, , 1985 and mouse mours [Szmigielski et al, 1982;. In a further study, exposure at 4 -5 W/kg, follymphoid cells [Meltz et al, 1989]. Lloyd et al [1984Lloyd et al [ , 1986 did not observe any effect of RF-field exposure lowed by application of a subcarcinogenic dose of a chemical carcinogen to the skin, a procedure repeated on chromosome aberration frequency in human cells.…”
Section: Cell Proliferative Responses and Transformationmentioning
confidence: 91%